The Effectiveness of Directed Reading Thinking Activity Assisted with Board Game Media on Fourth-Grade Reading Comprehension - Pradiningtyas, Nindhita; Cahyaningtyas, Andarini Permata (JOLLT Journal of Languages and Language Teaching, 2026)
Reading comprehension remains a persistent problem for Indonesian elementary students, as shown by the Computer-based National Assessment (ANBK) and the Progress in International Reading Literacy Study (PIRLS) outcomes. This situation calls for a reading strategy that can make students more active and engaged in constructing meaning from texts. Both Directed Reading Thinking Activity (DRTA) strategy and board game media have been proven effective separately and are potentially beneficial when integrated, yet studies on their combined use remain limited. This study aimed to examine the effectiveness of a DRTA strategy supported by board game media in improving fourth-grade students’ reading comprehension. The study employed a quantitative quasi-experimental design with a nonequivalent control group involving 38 fourth-grade students of SD Labschool UNNES. Data were collected through validated reading comprehension pre-test and post-test instruments and analyzed using the Wilcoxon Signed-Rank Test, Mann-Whitney U Test, and N-Gain analysis with SPSS 27. The findings showed that both groups improved, but the experimental group achieved stronger gains than the control group. Students taught through DRTA strategy supported by board game media were better able to make predictions, monitor understanding, confirm ideas with textual evidence, and develop responses across literal, inferential, and evaluative comprehension. These findings confirm that DRTA strategy supported by board game media is effective in improving fourth-grade students’ reading comprehension. This strategy also offers an interactive and meaningful alternative for elementary reading instruction.